Moving beyond the speed-price tradeoff - Acimovic, J; Lim, M; Mak, H (Massachusetts Institute of Technology, 2018)
In the early days of online retailing, e-commerce retailers fulfilled consumer demand from a small number of large-scale warehouses that carried a similar catalogue of items. Retailers stocked inventory for low-volume products in as few locations as possible while maintaining service levels that met customer expectations. It was a way to keep inventory costs low and take advantage of the economies of scale that accompany large fulfillment centers. Since consumers were willing to wait for their deliveries, proximity and speed were less important than cost savings. But the online retail market has changed. Today’s shoppers want more than low prices--they also want the products they order delivered quickly. To achieve same-day delivery, retailers are experimenting with new business and operations models, including using third parties (such as local city-specific delivery services), crowdsourcing (such as paying individuals by the task to shop for and deliver groceries), self-service (such as setting up physical lockers from where customers retrieve their packages), and even flying drones (whereby unmanned aerial vehicles can deliver packages in less than 30 minutes). At the same time, many retailers such as Amazon, Nordstrom, and Macy’s have recently redesigned their distribution networks. A growing number of omnichannel retailers are using their physical store networks to fulfill online orders (for example, shipping online customers’ orders from physical stores and allowing online customers to pick up their packages at physical stores), while online-only retailers are adding warehouses, particularly near major urban markets.